Problematyka równości i inkluzji społecznej osób z niepełnosprawnościami w dorobku normatywnym Rady Europy - Aleksander Gadkowski; Tadeusz Gadkowski (Acta Iuris Stetinensis, 2022)
The aim of this article is to present and analyze the most important provisions contained in the conventions of the Council of Europe with regard to rights of persons with disabilities. The abundant normative acquis of the Council does not offer a specific convention devoted this subject, but the issue of protecting the rights of persons with disabilities is governed by provisions of its various other conventions. The stipulations of the European Social Charter and the Revised European Social Charter are of crucial importance in this respect. With this in mind, the authors present the content and interpretation of Article 15 of both Charters and the position of the European Committee of Social Rights on this matter. The authors also point to the most important provisions of the Convention for the Protection of Human Rights and Fundamental Freedoms – in particular with reference to the prohibition of discrimination – and to the relevant case law of the European Court of Human Rights.